The Pulseq-CEST Library: definition of preparations and simulations, example data, and example evaluations - Liebeskind, Alexander; Schüre, Jan-Rüdiger; Fabian, Moritz; Weinmüller, Simon; Schünke, Patrick; Golkov, Vladimir; Cremers, Daniel; Zaiß, Moritz (Magnetic Resonance Materials in Physics Biology and Medicine, 2025)
Objectives: Despite prevalent use of chemical exchange saturation transfer (CEST) MRI, standardization remains elusive. Imaging depends heavily on parameters dictating radiofrequency (RF) events, gradients, and apparent diffusion coefficient (ADC). We present the Pulseq-CEST Library, a repository of CEST preparation and simulation definitions, including example data and evaluations, that provides a common basis for reproducible research, rapid prototyping, and in silico deep learning training data generation. Materials and methods: A Pulseq-CEST experiment requires (i) a CEST preparation sequence, (ii) a Bloch–McConnell parameter set, (iii) a Bloch–McConnell simulation, and (iv) an evaluation script. Pulseq-CEST utilizes the Bloch–McConnell equations to model in vitro and in vivo conditions. Using this model, a candidate sequence or environment can be held constant while varying other inputs, enabling robust testing. Results: Data were compared for amide proton transfer weighted (APTw) and water shift and B1 (WASABI) protocols using a five-tube phantom and simulated environments. Real and simulated data matched anticipated spectral shapes and local peak characteristics. The Pulseq-CEST Library supports similar experiments with common sequences and environments to assess new protocols and sample data. Discussion: The Pulseq-CEST Library provides a flexible mechanism for standardizing and prototyping CEST sequences, facilitating collaborative development. With the capability for expansion, including open-source incorporation of new sequences and environments, the library accelerates the invention and spread of novel CEST and other saturation transfer approaches, such as relayed NOEs (rNOEs) and semisolid magnetization transfer contrast (MTC) methods.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Computer assisted; Computer simulation; Image processing; Imaging; Magnetic resonance imaging; Phantoms; Software